1989
DOI: 10.4319/lo.1989.34.6.1062
|View full text |Cite
|
Sign up to set email alerts
|

Copepod diel migration, feeding, and the vertical flux of pheopigments.

Abstract: Feeding and diel vertical migration in the copepods Calanus pacijicus Brodsky and Metridia hens Boeck were examined during dusk and dawn in Dabob Bay, Washington. Both species migrated from below 75 m during the day into the upper 25 m at night. Feeding on phytoplankton was confined to periods spent in the surface layer.Metridia Iucens arrived in the surface 0.5 h after sunset, fed at high rates throughout the night until 1.0 h before sunrise, and then returned to depth. In contrast, C. paczjhs appeared in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 30 publications
4
45
1
Order By: Relevance
“…(Kleppel et al 1985, Stearns 1986, Stearns et al 1987, Durbin et al 1990), supporting Petipa's (1958) hypothesis of a die1 variation in filtering rate. Die1 variation in feeding rate appears to be controlled independently of diel vertical migration to and from the chlorophyll-rich surface layer (Stearns & Forward 1984a, b, Head et al 1985, Stearns 1986, Dagg et al 1989. Field studies have suggested that die1 feeding rhythms are reduced under low food availability (Boyd et al 1980, Dagg 1985, Dagg & Walser 1987, Daro 1988), but in the laboratory Durbin et al (1990) found that the diel feeding rhythm in A. tonsa persisted under both high and low food conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kleppel et al 1985, Stearns 1986, Stearns et al 1987, Durbin et al 1990), supporting Petipa's (1958) hypothesis of a die1 variation in filtering rate. Die1 variation in feeding rate appears to be controlled independently of diel vertical migration to and from the chlorophyll-rich surface layer (Stearns & Forward 1984a, b, Head et al 1985, Stearns 1986, Dagg et al 1989. Field studies have suggested that die1 feeding rhythms are reduced under low food availability (Boyd et al 1980, Dagg 1985, Dagg & Walser 1987, Daro 1988), but in the laboratory Durbin et al (1990) found that the diel feeding rhythm in A. tonsa persisted under both high and low food conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies have suggested that die1 feeding rhythms are reduced under low food availability (Boyd et al 1980, Dagg 1985, Dagg & Walser 1987, Daro 1988), but in the laboratory Durbin et al (1990) found that the diel feeding rhythm in A. tonsa persisted under both high and low food conditions. The stability of the behavior provided indirect evidence that diel feeding rhythms, like diel vertical migration, may reduce vulnerability of the copepods to visual predators (Frost 1988, Haney 1988, Bollens & Frost 1989, Dagg et al 1989.…”
Section: Discussionmentioning
confidence: 99%
“…The short term periodicity of fluxes was often on the order of 12 to 24 h. POC fluxes were generally higher during night period than during day with only rare exceptions (20 September for example). This diel periodicity of POC fluxes could be the result of the diel fluctuation in zooplankton grazing rate as evidenced by Welschmeyer et al (1984) or Dagg et al (1989) even if phaeopigment fluxes do not follow the same rhythm. A possible explanation of this discrepancy between organic carbon and phaeopigments may be the fact that phaeopigments are produced by micro and meso zooplankton with different sinking rates and could also be modified by photooxidation due to there long residence time in surface waters in stratified conditions, leading to colourless products (Cuny et al, 2002) which are included in the organic carbon measurement but not in phaeopigments.…”
Section: Short-term Variations (Wind Events Changing Water Masses Dmentioning
confidence: 99%
“…Furthermore, although we do not have direct information on phytoplankton community composition for either cruise, the phytoplankton community in Monterey Bay is generally dominated by diatoms during the seasons in which both of these cruises occurred (Garrison 1979;. Diatoms are especially susceptible to breakage during grazing, thus resulting in DON release via sloppy feeding (Dagg 1974;Lampert 1978). Third, high grazing rates are also suggested by the large changes in Chl a concentrations.…”
Section: Summary Of Nitrogen Flux-inmentioning
confidence: 99%
“…First, DON release resulting from NH up-ϩ 4 take and NH regeneration were all higher at night than dur-ϩ 4 ing the day; grazing rates tend to increase at night (Dagg et al 1989). Second, the large peak in DON release resulting from NH uptake at night also coincided with the peak in tion are often associated with high grazing activity (Goldman et al 1985).…”
Section: Summary Of Nitrogen Flux-inmentioning
confidence: 99%